Perfil Epidemiológico da morbimortalidade masculina em decorrência de violência na Paraíba:análise baseada em sistemas de informações - Lima, Elizabeth Alves de (2022)
This study aimed to describe the profile of male morbidity and mortality in Paraíba, as a result of aggression in the period of 2015 - 2020. The research was a cross-sectional observational study of a descriptive and quantitative nature, using secondary data obtained through the Hospital Information System (SIH) and Mortality Information System (SIM), in the DATASUS database, through the TABNET platform. The data were collected from the selection of the option external causes with geographic coverage in Paraíba, esulting in a total of 6957 deaths and 2084 hospitalizations, later, tables were generated resulting from the crossing of variables in the system platform. These tables were transcribed into Microsoft Excel software, where descriptive statistics were performed. The age group data were submitted to the calculation of Potential Years of Life Lost – PYLL, for which limits 1 and 70 were considered as upper and lower, respectively. The results of the descriptive analysis showed that the main cause of death by aggression among the male population of Paraíba is the shooting of a firearm (n = 5663; 81.40%), a result that is repeated when morbidity is also observed (n = 952; 45.68%). Dying by firearms fatally victmized especially young men with an average of 39.23 years of life lost, with death usually occurring around the age of 30. The brown population was the most prevalent victim in all types of aggression, mainly by firearms (n = 531), sharp or penetrating objects (n = 276), and physical force (n = 207). This study found that brown men aged around 30 years, are more prone to deaths and hospitalizations due to aggression, especially due to shootings.